Risk management in construction projects - Iqbal, Shahid; Choudhry, Rafiq M.; Holschemacher, Klaus; Ali, Ahsan; Tamošaitienė, Jolanta (Technological and Economic Development of Economy, 2015)
Risk management is an important field of construction industry and has gained more importance internationally due to the latest researches carried out on a large scale. However, this relatively new field requires more attention to bring some benefit. Construction projects are facing a number of risks which have negative effects on project objects such as time, cost and quality. This study is based on findings of a questionnaire-based survey on risk management in construction projects in Pakistan, reporting the significance of different type of risk, ultimate responsibility for them and the effectiveness of some most common risk management techniques practiced in the industry. Two types of risk management techniques were considered: preventive techniques which can be used before the start of a project to manage risks that are anticipated during the project execution; and remedial techniques that are used during the execution phase once a risk has already occurred. The study revealed that financial issues for projects, accidents on site and defective design are the most significant risks affecting most of construction projects. As further reported, the contractor is responsible for management of most risks occurring at sites during the implementation phase, such as issues related to subcontractors, labour, machinery, availability of materials and quality, while the client is responsible for the risks such as financial issues, issues related to design documents, changes in codes and regulations, and scope of work. Further reported results of the analysis demonstrate that the production of proper schedule by getting updated data of the project and guidance from previous similar projects are the most effective preventive risk management techniques while close supervision and coordination within projects are the most effective remedial risk management techniques. It may be concluded that the most significant risks must be managed with greater effort to reduce/eliminate their effects on the project. As the study concludes, preparation of a proper schedule and good coordination during the implementation stage are very important as they may help project managers to focus on critical areas for better management of projects in Pakistan.